Analysis of Household Sanitation and Community Behavior using the EHRA Method in the Working Area Kawangkoan Public Health Center - Timontiling , Heldy Claudya; Pinontoan, Odi (Science Tech Group, 2026)
Household sanitation and community behavior are the main determinants of environmental health that contribute to the incidence of environmentally-based diseases. This study aims to analyze household sanitation conditions, community behavior, and their relationship to environmental health risks using the Environmental Health Risk Assessment (EHRA) method in the Kawangkoan Community Health Center (Puskesmas) working area. The study used a descriptive analytical design with a cross-sectional approach to 100 household respondents. Data were collected through the EHRA questionnaire and analyzed using the chi-square test and multivariate analysis. The results showed that the majority of respondents were in the risky sanitation and risky behavior categories. Statistical tests showed a significant relationship between household sanitation and environmental health risks, as well as between community behavior and environmental health risks. Household sanitation variables and behavior simultaneously influence the level of environmental health risks. This study emphasizes the importance of STBM-based promotive and preventive interventions to reduce environmental health risks at the household level. This study supports the achievement of the Sustainable Development Goals, particularly SDG 6 (ensuring availability and sustainable management of water and sanitation for all) and SDG 3 (promoting health and well-being), by providing evidence-based insights to strengthen sanitation improvement strategies and disease prevention efforts in community settings.